Gambaran spesies candida penyebab kandidiasis vulvovaginalis rekuren di RSUP Haji Adam Malik Medan - Deryne Anggia Paramita; Kristina Nadeak; Richard Hutapea (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Introduction : Recurrent vulvovaginal candidiasis (RVVC) is an episode four times or more vulvovaginal candidiasis within 12 months, nearly 85% up to 95% are caused by Candida albicans. The rest 10% to 20% are caused by non-albicans species. RVVC caused by non-albicans species is clinically indistinguishable from that caused by Candida albicans, and non-albicans species usually are more resistant to therapy.Objective : To reveal which is the most Candida species that cause recurrent vulvovaginal candidiasis in Haji Adam Malik General Hospital MedanMethod : Cross sectional study was conducted in August-September 2012, involving 30 people with RVVC. To each subject, vaginal swab examination, culture and fermentation test was done to see Candida species.Result : The study found the following results: Candida albicans (43.3%) Candida parapsilosis (16.6%), Candida tropicalis (10%), Candida glabrata (6.7%), Candida lusitinae (6.7%), Candida guiliermondi (6.7%), Candida kefyr (6.7%), Candida catenulata (3.3%)Conclusion : Candida albicans is the most widely Candida species that cause RVVC in Haji Adam Malik General Hospital Keywords: recurrent candidiasis vulvovaginalis, Candida species